Peroxiredoxin 6 Applied after Exposure Attenuates Damaging Effects of X-ray Radiation in 3T3 Mouse Fibroblasts - Elena G. Novoselova; Mars G. Sharapov; Sergey M. Lunin; Svetlana B. Parfenyuk; Maxim O. Khrenov; Elvira K. Mubarakshina; Anna A. Kuzekova; Tatyana V. Novoselova; Ruslan G. Goncharov; Olga V. Glushkova (MDPI AG, 2021)
Although many different classes of antioxidants have been evaluated as radioprotectors, none of them are in widespread clinical use because of their low efficiency. The goal of our study was to evaluate the potential of the antioxidant protein peroxiredoxin 6 (Prdx6) to increase the radioresistance of 3T3 fibroblasts when Prdx6 was applied after exposure to 6 Gy X-ray. In the present study, we analyzed the mRNA expression profiles of genes associated with proliferation, apoptosis, cellular stress, senescence, and the production of corresponding proteins from biological samples after exposure of 3T3 cells to X-ray radiation and application of Prdx6. Our results suggested that Prdx6 treatment normalized p53 and NF-κB/p65 expression, p21 levels, DNA repair-associated genes (XRCC4, XRCC5, H2AX, Apex1), TLR expression, cytokine production (TNF-α and IL-6), and apoptosis, as evidenced by decreased caspase 3 level in irradiated 3T3 cells. In addition, Prdx6 treatment reduced senescence, as evidenced by the decreased percentage of SA-β-Gal positive cells in cultured 3T3 fibroblasts. Importantly, the activity of the NRF2 gene, an important regulator of the antioxidant cellular machinery, was completely suppressed by irradiation but was restored by post-irradiation Prdx6 treatment. These data support the radioprotective therapeutic efficacy of Prdx6.